Pattern of minor element enrichment in columbites: A synchrotron radiation X-ray fluorescence (SRXRF) study - Mirao, J.P. (2012)
The pattern of minor elements incorporation in columbites from granitic pegmatites of Alto Ligonha, Mozambique, was disclosed on the basis of synchrotron radiation X-ray fluorescence (SRXRF) data. Major elements (Fe, Mn, Nb, Ta) were analyzed with an electron microprobe (EPMA). Minor and trace element contents display a common general trend pointing towards the preferential uptake of metals that minimize the stress induced in the host crystal structure by the non-commensurability of cations with distinct valences and ionic radii. The simultaneous incorporation of Ti, Zr, U, Pb, Y and W assures electrostatic equilibrium, being conditioned by the dominant presence of niobium, while Sc concentrates in solid solutions with low Nb/(Nb+Ta) ratios.